اردو افسانے میں تہذیبی علامتوں اور افسانوی تکنیکوں کا باہمی تعلق: پاکستانی تہذیبی تشخص کا بین المتنی تجزیہ: Urdu Afsanay Mein Tahzeebi Alamaton Aur Afsanvi Taknikon ka Bahami Taalluq: Pakistani Tahzibi Tashakhus ka Bain ul Matni Tajziya - Abbas, Dr. Zaheer (Zoraiz, 2025)
This research explores the intricate relationship between cultural symbols and narrative techniques in Urdu short stories, with a specific focus on how these elements contribute to the construction of Pakistani cultural identity. The study adopts an intertextual approach, analyzing how Urdu fiction interacts with historical, religious, folkloric, and socio-political texts to reflect the nation's evolving identity. By examining selected works of key Pakistani short story writers such as Intizar Hussain, Ahmed Nadeem Qasmi, Khalida Hussain, and Asad Muhammad Khan, the research highlights how fiction is not only a reflection of society but also a space for reconstructing and questioning cultural norms. The study further investigates how literary devices such as symbolism, stream of consciousness, fragmented narrative, and allegory serve as tools for embedding cultural consciousness within fictional frameworks. The analysis reveals that Urdu fiction, while adopting diverse narrative strategies, often draws on deep-rooted cultural symbols to represent and critique Pakistani society. The research aims to contribute to the understanding of how literature, especially fiction, functions as a vessel for preserving and challenging cultural identity in a postcolonial, globalized context.